Reforming the Regulation of Therapeutic Products in Canada: The Protecting of Canadians from Unsafe Drugs Act (Vanessa's Law) - Katherine Fierlbeck (McMaster University Library Press, 2016)
Enacted November 2014, Vanessa's Law amends the Food and Drugs Act to give Health Canada greater powers to compel the disclosure of information, recall drugs and devices, impose fines and injunctions, and collect post-market safety information. The Act amends seriously outdated legislation that had been in place since 1954. While the explicit goals of the Act are to improve patient safety and provide transparency, it also establishes a regulatory framework that facilitates investment in the burgeoning field of biotechnology. While regulatory reform was already on the public agenda, public awareness of litigation against large pharmaceutical firms combined with the championing of the legislation by Conservative MP Terence Young, whose daughter Vanessa died from an adverse drug reaction, pushed the legislation through to implementation. Many key aspects of the Act depend upon the precise nature of supporting regulations that are still to be implemented. Despite the new powers conferred by the legislation on the Minister of Health, there is some concern that these discretionary powers may not be exercised, and that Health Canada may not have sufficient resources to take advantage of these new powers. Given experience to date since enactment, the new legislation, designed to provide greater transparency vis-à-vis therapeutic products, may actually have a chilling effect on independent scrutiny. La Loi de Vanessa, qui a reçu la Sanction royale en novembre 2014, modifie la Loi sur les aliments et drogues pour donner à Santé Canada plus de possibilités d'imposer la divulgation d'information, de retirer de la vente des médicaments et dispositifs, d'appliquer amendes et injonctions, et de collecter des informations sur la sécurité après la mise sur le marché. La Loi représente une modification en profondeur d'une législation surannée, en place depuis 1954. Si l'objectifs annoncé de la Loi sont d'améliorer la sécurité des patients et la transparence, elle établit aussi un cadre réglementaire facilitant l'investissement dans le domaine bourgeonnant des bio-technologies. Le besoin d'une réforme du cadre réglementaire se faisait déjà sentir, mais le passage de la Loi a été accéléré par la combinaison d'une sensibilisation du public aux actions en justice contre de grandes firmes pharmaceutiques et du parrainage de la législation par le député Conservateur Terence Young, dont la fille Vanessa est morte d'une réaction indésirable à un médicament. La Loi va dépendre crucialement de la nature précise des réglementations l'accompagnant, toujours en discussion. Malgré les nouveaux pouvoirs conférés par la Loi au Ministre de la santé, on peut craindre que ces pouvoirs discrétionnaires ne soient pas utilisés dans les faits et que Santé Canada manquent de ressources pour en tirer parti. En se fondant sur l'expérience depuis la Sanction royale, la nouvelle législation, bien que censée augmenter la transparence sur les produits thérapeutiques, pourrait en fait bloquer l'investigation indépendante.